Productivity, Matchability and Intermediation in Production Networks - Kalina Manova; Andreas Moxnes; Oscar Perelló (CESifo GmbH, 2025)
This paper examines intermediation in production networks to unpack the firm attributes and matching costs that govern firm-to-firm networks and the gains from trade. Exploiting rich customs data for Chile, we show that exporters of all sizes use intermediaries, mix trade modes across buyers, and set lower prices on intermediated flows. We rationalize these facts in a model of network formation with suppliers of heterogeneous productivity and matchability, buyers of heterogeneous productivity, and intermediaries that reduce matching costs for a brokerage fee. Empirical evidence on trade activity across firms and countries corroborates the model, and informs how geographic distance, logistics and customs efficiency, formal institutions, and cultural-linguistic similarity shape network costs. Model estimation reveals that sellers' attributes are negatively correlated, such that intermediaries enable highly productive sellers with low matchability to reach smaller buyers. This amplifies the welfare gains from intermediation due to wider and deeper network connectivity.
Keywords: F10; F12; F14; F23; L11; L14; L81; 330; production networks; intermediation; productivity; matching costs